UMP remains tradition of eating in trays to close ukhuwah - Mimi Rabita, Abdul Wahit (2023)
KUANTAN, 8 March 2023 - Universiti Malaysia Pahang (UMP) continues to maintain its tradition during Ramadan by providing free iftar meals using the trays to its residents who break their fast at the UMP Mosque, Gambang and Pekan Campuses for more than ten years.